Sensor placement based on static finite element data of cable stayed bridge - Mohammed, Mohammed Idris; Sulaeman, Erwin; Mustafa, Faizal; Mohd Ariffin, Mohd Khairol A. (International Journal of Emerging Technology and Advanced Engineering (IJETAE), 2017)
Bridges are essential great value infrastructure which provide services for a long period of time. Their age increases over the time so as the complexity of its operating and maintaining activities. The present study is considering cable stayed Penang (I) bridge in Malaysia which has 440 m spans long. Hence, the paper initially aims to propose location of sensors based on a dead load condition. A finite element i.e. static analysis is used to identify the critical grid points at the bridge’s members. The study recommended 18 places of sensors, which are located at the spans, cables and piers of the bridge.